Persepsi Masyarakat terhadap Penataan Kabel Utilitas Bawah Tanah di Jalan Diponegoro Kota Bandung - Yudha Setiadi; Helmi Mustafa; Moch Salik Munawar; Nayla Fitri Ramadhanie (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This research is motivated by the problem of disorganized overhead cables in Bandung City, which disrupts urban aesthetics and public safety. The government responded through the Passive Telecommunications Infrastructure (IPT) Program using an underground ducting system. The study aims to analyze the level of public knowledge and perception regarding the objectives and benefits of cable management on the strategic Diponegoro Street. A quantitative descriptive-analytical approach was utilized, with data collected through questionnaires from 55 road users. The 15-item research instrument was proven valid and reliable, with a Cronbach’s Alpha of 0.941. Findings reveal that public perception is categorized as very positive and high overall. The "Right Target" and "Right Policy" dimensions received the highest appreciation, as respondents recognized the program’s urgency for Smart City acceleration and the reliability of the Electronic-Based Government System (SPBE). Despite short-term environmental stress during construction, the benefits of visual aesthetics and psychological safety dominate public perception. The implications of this study provide a scientific basis for the government to continue and expand cable management policies to other vital corridors to create modern, safe, and sustainable urban spaces.